German global soft power, 1700-1920 - McLelland, Nicola (Amsterdam University Press, 2016)
This article provides the first overview of the reach and 'soft power' of German language and culture in Europe and beyond, from 1700 to 1920, shortly after the end of the First World War. Besides the role of the state (weak, until deliberate policies began to be formulated from the late nineteenth century), the article shows the role of language societies, religious, educational and scientific institutions, and other sociocultural and political factors, including migration and colonization, in promoting German 'soft power' in other parts of Europe, in the Americas, Africa and China. The changing status of German language and culture in these parts of the world and the extent of local and 'home' support, through explicit policy or otherwise, for German as a first, foreign or additional language abroad is also considered.